Learn social engineering from scratch (Packt Publishing, 2018)
"Welcome to this comprehensive course on social engineering! In this course, you will start as a beginner with no previous knowledge about penetration testing or hacking, we will start with the basics of social engineering, and by end of it you'll be at an advanced level being able to hack into all major operating systems (Windows, OS X, and Linux), generate different types of trojans, and deliver them using smart social engineering techniques. This course is focused on the practical side of penetration testing without neglecting the theory. Before jumping into penetration testing, you will first learn how to set up a lab and install needed software to practice penetration testing safely on your own machine. Finally, at the end of the course, you will learn how to protect yourself and your systems from these attacks. All the attacks in this course are practical attacks that work against real computers. In each technique you will understand the theory behind it and how it works, then you'll learn how to use that technique in a real-life scenario, so by the end of the course you'll be able to modify these techniques or combine them to come up with more powerful attacks and adapt them to different scenarios and different operating systems."--Resource description page